심혈관질환 증상이 없는 성인에서 목동맥 FDG 섭취와 심혈관계 질환 위험인자 간의 관계 고찰 - Lee, Dong Hyun (The Graduate School, Ajou University, 2015)
Relation between carotid artery FDG uptake and cardiovascular risk in asymptomatic adults We investigated the relation between carotid artery FDG uptake and cardiovascular risk based on the Framingham risk score (FRS), and evaluated the possible role of FDG uptake in terms of risk stratification of asymptomatic adults. We evaluated 290 adults who underwent FDG PET/CT as part of general health screens. We calculated target-to-background ratios, corrected for pre-scan blood glucose levels, and obtained “TBRglu” values for both common carotid arteries. The FRS and the presence/absence of metabolic syndrome were recorded for each subject. Relationships among TBRglu values, metabolic syndrome status, and clinical parameters were assessed. Carotid artery FDG uptake was significantly associated with clinical risk factors. Stepwise multiple regression analysis revealed that triglyceride levels, diabetes, and metabolic syndrome were independent determinants of high TBRglu. Of subjects with metabolic syndrome, those exhibiting high carotid artery FDG uptake had significantly higher levels of high sensitivity C-reactive protein (hsCRP). In subjects who did not have metabolic syndrome, FRS were significantly elevated in those exhibiting high carotid artery FDG uptake compared to those with low uptake (13.1 ± 7.0 vs. 8.2 ± 7.4), as was also true of subjects with the syndrome (21.8 ± 16.0 vs. 13.5 ± 11.9). High carotid FDG uptake is significantly associated with clinical risk factors and a greater FRS. Of subjects with metabolic syndrome, those with high carotid uptake had significantly higher hsCRP concentrations and FRSs. Therefore, carotid artery FDG activity may serve as a possible biomarker allowing cardiovascular risk stratification of asymptomatic populations.
학위논문(석사)--아주대학교 일반대학원 :의학과,2015. 2
Keywords: atherosclerosis; carotid arteries; 동맥경화증; 대사증후군